Myocardial Infarction amongst the patients presenting with chest pain in an Emergency Department of a Tertiary Care Hospital in Western Nepal: A descriptive cross-sectional study - Parajuli, Angana; Guragain, Sandeep; Bastakoti, Navaraj; Subedi, Ashim; Dhakal, Saraswati; Ranjan Psd Koirala, Rupak (Nepal Journal of Medical Sciences, 2026)
Introduction: Chest pain is one of the symptoms which bring patient to the Emergency Department. Myocardial infarction is the most significant clinical presentation of Acute Coronary Syndrome and cause of morbidity and mortality among the global population. This study aims to identify the occurrence of Myocardial Infarction and investigate its relationships with demographic and cardiac risk factors, and characteristics of chest pain. Methods: A prospective cross-sectional study was carried out among 113 patients in the Emergency Department of Manipal Teaching Hospital, Nepal. For categorical variables, descriptive statistics, including frequency and percentage, were presented. The Chi-square test, Independent Samples Test were employed for inferential analysis. A p-value of less than 0.05 was considered to be as significant. Results: Among 113 patients who attended with chest pain, 31 patients had a myocardial infarction. Age, gender and occupation showed no significant association in Myocardial Infarction Troponin-positive patients also had a higher prevalence of smoking and dyslipidemia, although it was not statistically significant in our study. Nonetheless, cardiovascular disease was of significant association with myocardial infarction (p=0.004). ECG results showed a close correlation with MI where 62.9 % of troponin-positive patients reported STEMI (p<0.0001). The most common abnormality in NON-STEMI patients was T-wave inversion (61.5%). Conclusions: Myocardial infarction was frequent occurrence in patients who reported chest pain in this tertiary care unit. The study indicates that combining clinical history, risk factor evaluation, ECG interpretation, and cardiac biomarkers are significant in early diagnosis and management of MI